Tinjauan Hukum Tindak Pidana Plagiarisme Karya Ilmiah: 46-57 - Muhammad Perdana Syah; Suriani Siagian (Jurnal Hukum dan Demokrasi (JHD), 2023)
Plagiarism is an offense and an ornament to science. Plagiarists steal the work of other authors or what is commonly called cheating or plagiarizing without citing the origins of the original author. Plagiarism is an act that is vulnerable to criminal activity and this problem must be considered in as much detail as possible. The act of plagiarism is recognized as an act that is disapproved and contrary to the scientific spirit in the academic world in universities. Several types of plagiarism can be distinguished by intentional or unintentional plagiarism motivation, ways of committing plagiarism include handwriting, inappropriate paraphrasing, and summaries, plagiarism itself can be said to be recycling text, redundant or duplicate publications, data fragmentation . The purpose of this study is to find out the legal arrangements for plagiarism of scientific work in tertiary institutions and to find out the legal consequences for perpetrators of the crime of plagiarism of scientific work in tertiary institutions. The research method used by the author is normative research method which positions the law as a building system of norms. There is no law that specifically regulates plagiarism, but someone who commits plagiarism or is called a plagiarist is regulated in Article 1, Minister of National Education Regulation number 17 of 2010 concerning the prevention and control of plagiarism in tertiary institutions. There are several reasons for someone to commit plagiarism, such as the convenience obtaining information via the internet, pressure on academic assignments, poor writing skills, rushing to write under pressure, lack of knowledge and understanding of how to rewrite original references, misunderstandings to self-understand plagiarism, and habitual cheating or plagiarism, such as avoiding theft intellectual, do good writing i.e. quote and paraphrase, and try the same thing or detect plagiarism in many ways like using plagiarism apps or turnitin. Keywords: plagiarism, legal actions, scientific works, norms